RETRACTED: Studying the effectiveness of comprehensive wastewater treatment - Izbullaeva Malika; Amonov Mukhtor; Jalilov Sherali (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001